Tafsir Rahmat: Historical Traces and Background of Oemar Bakry’s Work - Haikal Al Fiqri (UIN Imam Bonjol Padang, 2025)
Tafsir Rahmat by Oemar Bakry is one of the scholarly legacies of Indonesian Islamic scholars that deserves to be studied and appreciated. This tafsir employs a communicative and informative language style, making it easier for readers to understand the meanings of Qur’anic verses. Its emergence served as a response to various socio-religious issues of the time, which had not been adequately addressed by previous Qur’anic interpretations. This study uses a library research method with a descriptive-analytical approach-collecting data and analyzing it as the basis for drawing conclusions. The findings show that Tafsir Rahmat consists of one volume, written over a period of three years (1981-1983), published in 1984, and translated into Sundanese in 1986 by M. Sulaiman in three volumes. It falls under the category of tafsir bil al-ra'yi, with a lughawi (linguistic) style, and follows the ijmali (global) method. This study contributes to revealing the significance of Tafsir Rahmat as part of the communicative and contextual heritage of Nusantara Qur’anic exegesis. Moreover, it clarifies the interpretive methods used by Oemar Bakry and highlights the relevance of his work to the socio-religious dynamics of his time, while also enriching the body of local tafsir literature that has long been underrepresented in academic discourse.